2019
DOI: 10.1002/hbm.24708
|View full text |Cite
|
Sign up to set email alerts
|

The joint effect of aging and HIV infection on microstructure of white matter bundles

Abstract: Recent evidence suggests the aging process is accelerated by HIV. Degradation of white matter (WM) has been independently associated with HIV and healthy aging. Thus, WM may be vulnerable to joint effects of HIV and aging. Diffusion‐weighted imaging (DWI) was conducted with HIV‐seropositive (n = 72) and HIV‐seronegative (n = 34) adults. DWI data underwent tractography, which was parcellated into 18 WM tracts of interest (TOIs). Functional Analysis of Diffusion Tensor Tract Statistics (FADTTS) regression was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
4
10
0
Order By: Relevance
“…Our HIV + participants had greater than normal age-dependent declines in FA in the ACR, CC and SS, regardless of MJ usage; this is consistent with findings in prior DTI studies (36,48). In addition, we observed greater than normal age-related FA decline in the EC and SLF of MJ users regardless of HIVserostatus, which is consistent with the greater than normal age-related FA decline in multiple white matter regions in MJ users (24).…”
Section: Age-related and Mj-related Changes In Dti Metrics In Hiv + Isupporting
confidence: 90%
“…Our HIV + participants had greater than normal age-dependent declines in FA in the ACR, CC and SS, regardless of MJ usage; this is consistent with findings in prior DTI studies (36,48). In addition, we observed greater than normal age-related FA decline in the EC and SLF of MJ users regardless of HIVserostatus, which is consistent with the greater than normal age-related FA decline in multiple white matter regions in MJ users (24).…”
Section: Age-related and Mj-related Changes In Dti Metrics In Hiv + Isupporting
confidence: 90%
“…Our HIV+ participants had greater than normal age-dependent declines in FA, suggesting accelerated age-related loss of fiber integrity, in the corpus callosum regardless of MJ usage; this finding is consistent with those in prior DTI studies [ 40 , 69 ]. In addition, we observed greater than normal age-related FA decline in the SLF and EC of MJ users regardless of HIV serostatus, which is also consistent with the greater than normal age-related FA decline in multiple white matter regions in MJ users [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another recent study of virally suppressed patients reported that white matter alterations were present in patients with HAND, but HIV patients without cognitive impairment had similar white matter measures compared to uninfected controls [ 21 ]. Furthermore, more pronounced white matter alterations were observed in older patients with HIV [ 22 ], which may reflect accelerated brain aging. White matter alterations are also associated with impairment of several cognitive domains in patients with controlled infection and no other medical comorbidities [ 23 ].…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%